(untitled) (Research, Society and Development, 2022)
The aim of this study is to evaluate by finite element analysis different techniques of totally edentulous maxilla rehabilitation, considering implants, bone tissue, metallic infra-structure, and prosthetic abutments characteristics, by means of a three-dimensional model. Stress distribution on bone tissue, implants, and abutments was analyzed with four configurations (six implants axially installed, all-on-four technique, M-4 technique, and four conventional implants with two zygomatic implants). Greater tension on bone tissue were found around distal implants, in all treatment groups, but not exceeding resistance limits of cortical bone. Von Mises stress was higher on the distal region of distal implants of all-on-four and M-4 techniques. Higher stress concentration was seen on angled abutments of zygomatic implants. The highest values of minimal compression stresses were concentrated on peri implant-bone tissue, especially in the model of All-on-4. Therefore, the present finite element analysis revealed that the four configurations of treatment (six implants axially installed, all-on-four technique, M-4 technique, and four conventional implants with two zygomatic implants) for the totally edentulous maxilla are feasible and safe, from a biomechanical point of view.